Edição de material instrucional para EAD baseada em estratégias cognitivas - Orbolato, Rafael Godoi (2003)
A lack of support to teachers in the instructional material creation was verified during a research with computer-based distance learning environments, this support being related both to technological and pedagogical aspects. To propose a support in these two fields, technology and pedagogy, this work analyzed the learning theories. From this analysis arose the opportunity to adapt the cognitive strategies' ideas as a pedagogical support to the teacher in the content organization of the instructional material. In addiction, as the material format to the Web has a different structure from the conventional one, it was defined a basic set of usability directives and explanations about these differences, as another form of support to the teacher. The Cognitor, an instructional material creation tool was developed, joining its technological support in the material creation for the Web, with the pedagogical support mentioned previously.